ANALISIS YURIDIS TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA BAGI DIRI SENDIRI OLEH ANAK (Studi Putusan Nomor 1/Pid.Sus-Anak/2019/PN Sgr) - I Gst. Agung Komang Yoga Tri Pandita; Made Sugi Hartono; Ni Ketut Sari Adnyani (Universitas Pendidikan Ganesha, 2023)
This study aims to analyze the judge considerations in decision Number 1/Pid.Sus-Anak/2019/PN Sgr and the importance of diversion in handling a child case, using normative juridical research methods. As for the results of the research, first is the application of criminal law in Decision Number 1/Pid.Sus-Anak/2019/PN.Sgr is basically correct, where both the form of the indictment and the articles used against the child's actions have fulfilled the elements in the provisions of the article in question. set. However, this decision shows that judges tend to be negligent in interpreting the provisions of Article in Law No. 11 of 2012 concerning the Juvenile Criminal Justice System, so that judges are indicated to have ignored the provisions regarding the diversion policy, even though based on the results of the analysis it is known that, child has met the requirements to seek diversion. The result of the second research is that Diversion has an important meaning, especially in handling cases of narcotics abuse by children, such as the case in Decision Number 1/Pid.Sus-Anak/2019/PN.Sgr. Whereas by maximizing diversion efforts can prevent children from formal criminal justice which often creates bad experiences in the form of negative stigma from society, as well as minimizing recidivism because the punishment carried out is in line with the purpose of the punishment itself which not only protects the community but also repairs the perpetrators, so that this diversion is felt to provide the value of justice, legal certainty and expediency.